STUDI TENTANG SONGKET SESAMPIANG PENGHULU MINANGKABAU DI KECAMATAN KOTO TANGAH PADANG: BENTUK, NAMA MOTIF DAN NILAI BUDAYA - WITRI AFRIANA DEWI, Drs. Ajusril S, Eliya Pebriyeni, S.Pd, M.Sn (Serupa The Journal of Art Education, 2014)
This study is aims to: 1) Describe the shape of the design of Songket sesampiang Penghulu Koto Tangah, 2) Describe the name of the design of songket sesampiang Penghulu Koto tangah, and 3) Describe the value of the culture of songket sesampiang Penghulu Koto Tangah. This research is a qualitative description. The data sources are the primary source in tell a directly by the informan, while secondary data is the documentation and bibliography. The data was collected through observation, interviews, documentation. The findings of the study are in of songket Sesampiang in Koto Tangah is the Balapak with the shape of it is of nature design (Flora and Fauna) and geometry. It is have 8 (eight) names are Pucuak Rabuang, sajamba makan, balah kacang, saik galamai, barantai, itiak pulang patang, mato ayam, bungo tanjung.Kata kunci : Songket sesampiang, , Bentuk Motif, Nama Motif, Nilai Budaya.